(untitled) (Research, Society and Development, 2022)
Currently, there is a great concern on the part of consumers to purchase nutritious, healthy products that bring health benefits, with different flavors and above all, safe for consumption, being a market trend and, as yogurt ice cream is increasingly being appreciated in Brazil, the present study aimed to a) determine the ideal concentration of ginger to be added to frozen yogurt, b) determine the concentration of prebiotics in frozen yogurt added with ginger and c) study the feasibility of lactic cultures, the contents of bioactive compounds and the antioxidant capacity of symbiotic frozen yogurt added with ginger. It was found that the use of 0.8% and 1.0% of ginger added before or after the maturation of the syrup did not influence the preference of frozen yogurt. The addition of prebiotics, alone or in combination, influenced the pH, the sensory attributes of color and flavor and the overrun, with the use of 2% inulin providing higher levels of phenolic compounds. In view of the above, it is concluded that it is feasible to produce symbiotic frozen yogurt added with ginger. Thus, the ideal amounts of ginger and prebiotic to be added to the product are 1% and 2%, respectively.